Immunomodulation of human T cells by microbubble-mediated focused ultrasound - Baez, Ana; Singh, Davindra; He, Stephanie; Hajiaghayi, Mehri; Gholizadeh, Fatemeh; Darlington, Peter J.; Helfield, Brandon (Frontiers in Immunology, 2024)
While met with initial and ground-breaking success targeting blood borne cancers, cellular immunotherapy remains significantly hindered in the context of solid tumors by the tumor microenvironment. Focused ultrasound, in conjunction with microbubbles, has found tremendous potential as a targeted and local drug/gene delivery technique for cancer therapy. The specific immunomodulating effects of this technique on immune cells, including T-cells, remain unexplored. Here, with freshly isolated human immune cells, we examine how focused ultrasound can viably modulate immune cell membrane permeability and influence the secretion of over 90 cytokines, chemokines and other analytes relevant to a potent immune response against cancer. We determine that microbubble-mediated focused ultrasound modulates the immune cell secretome in a time-dependent manner -ranging in 0.1-3.6-fold changes in the concentration of a given cytokine compared to sham controls over 48 hours post-treatment (e.g. IL-1β, TNF-α, CX3CL1, CCL21). Further, we determine the general trend of a negative correlation between secreted cytokine concentration and viable ultrasound-assisted membrane permeability with negligible loss of cell viability. Taken together, the data presented here highlights the potential of microbubble-mediated focused ultrasound to viably enhance T-cell permeability and modulate key pro-immune pathways, offering a novel approach to augment targeted cellular therapies for solid tumors.